An investigation of truck jack-knifing using simulation software - Tan, Kai Hou. (2010)
A literature review of the causes and the theory of jackknifing were undertaken. Tractor semitrailer jackknifing are often caused by maneuvers such as braking with subsequent brake lock-up, from suddenly steering into a turn where the cornering may lead to lateral wheel skidding, or from some combination of these factors. In conjunction with the Port of Singapore Authority (PSA), accidents that resulted in truck jackknifing are being studied and reconstructed using simulation software. Jackknife prevention measures are determined based on the simulation result. In the simulation, the tractor semitrailer is modeled as two rigid bodies hinged together and in-plane motion. Explicit results are derived for the pre- and post-jackknifed vehicle speeds and steering angle as a function of the system parameters. Further, results of the case study for a tractor semitrailer initially in straight line motion show the sensitivity of the velocities to a range of steering conditions. The safe, unsafe and jackknife range are explicitly defined. The analysis performed on the simulation results suggested that low steering angle and speed have a very positive influence on safety. In addition, it is the safest to keep the speed below 21 km/h and steer no more than 13 degree during maneuver. While it is difficult to evaluate the accuracy of the simulation results, this study serves as a guide to physical jackknife analysis.